因式分解m²乘n²
因式分解m²乘n²
[x(x^2y^2-xy)-y(x^2-x^3y)]÷3x^2y=[x^2y(xy-1)-x^2y(1-xy)]÷3x^2y=2x^2y(xy-1)÷3x^2y=2/3(xy-1)。(-5a)^5b^3c÷[(15a)^4b^2]=-5^5/(3^4*5^4) abc=-5/81 abc。(-x+3y)(-x-3y)=(-x)^2-(3y)^2=x^2-9y^2。x^2-4y^2=(x+2y)(x-2y)。16x^2-24x+9=(4x)^2-2(4x)3+3^2=(4x-3)^2。(m+n)^2-(m+n)(2m-n)=(m+n)(m+n-2m+n)=(m+n)(2n-m)=2n^2+mn-m^2。
導讀[x(x^2y^2-xy)-y(x^2-x^3y)]÷3x^2y=[x^2y(xy-1)-x^2y(1-xy)]÷3x^2y=2x^2y(xy-1)÷3x^2y=2/3(xy-1)。(-5a)^5b^3c÷[(15a)^4b^2]=-5^5/(3^4*5^4) abc=-5/81 abc。(-x+3y)(-x-3y)=(-x)^2-(3y)^2=x^2-9y^2。x^2-4y^2=(x+2y)(x-2y)。16x^2-24x+9=(4x)^2-2(4x)3+3^2=(4x-3)^2。(m+n)^2-(m+n)(2m-n)=(m+n)(m+n-2m+n)=(m+n)(2n-m)=2n^2+mn-m^2。
![](https://img.51dongshi.com/20250107/wz/18421783452.jpg)
計算:[x(x^2y^2-xy)-y(x^2-x^3y)]÷3x^2y=[x^2y(xy-1)-x^2y(1-xy)]÷3x^2y=2x^2y(xy-1)÷3x^2y=2/3(xy-1)(-5a)^5b^3c÷[(15a)^4b^2]=-5^5/(3^4*5^4) abc=-5/81 abc(-x+3y)(-x-3y)=(-x)^2-(3y)^2=x^2-9y^2 x^2-4y^2=(x+2y)(x-2y)16x^2-24x+9=(4x)^2-2(4x)3+3^2=(4x-3)^2(m+n)^2-(m+n)(2m-n)=(m+n)(m+n-2m+n)=(m+n)(2n-m)=2n^2+mn-m^2
因式分解m²乘n²
[x(x^2y^2-xy)-y(x^2-x^3y)]÷3x^2y=[x^2y(xy-1)-x^2y(1-xy)]÷3x^2y=2x^2y(xy-1)÷3x^2y=2/3(xy-1)。(-5a)^5b^3c÷[(15a)^4b^2]=-5^5/(3^4*5^4) abc=-5/81 abc。(-x+3y)(-x-3y)=(-x)^2-(3y)^2=x^2-9y^2。x^2-4y^2=(x+2y)(x-2y)。16x^2-24x+9=(4x)^2-2(4x)3+3^2=(4x-3)^2。(m+n)^2-(m+n)(2m-n)=(m+n)(m+n-2m+n)=(m+n)(2n-m)=2n^2+mn-m^2。
為你推薦